Development of environmental contours for first-year ice ridge statistics. (November 2020) - Chai, Wei; Leira, Bernt J.; Naess, Arvid; Høyland, Knut; Ehlers, Sören
Highlights: The concept of environmental contour is introduced for first-year sea ice ridge statistics. Different forms of environmental contours are generated. Influence of the correlation relationship and number of ice ridge events on environmental contours was studied. Abstract: Ice ridges represent a major threat to ships and offshore structures in areas with sea ice but no icebergs, since they frequently determine and govern the structural design loads. This work focuses on the development of environmental contours for first-year sea ice ridge statistics, which are able to represent the key parameters that will influence the extreme loads that would be acting on ice-capable vessels sailing in Arctic regions. Based on the inverse first order reliability method (IFORM), the development of environmental contours to be applied for the reliability-based design of ice-capable vessels in Arctic regions is elaborated. The number of relevant parameters and hence the dimension of the space containing the environmental contour will depend on the particular ice-vessel interaction model that is to be applied. Furthermore, the influence from the degree of correlation between the environmental parameters as well as from the number of ship-ice ridge interaction during the voyage on the environmental contour shapes are studied.